2020
DOI: 10.1080/19942060.2020.1830857
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer through converging-diverging channels using Adomian decomposition method

Abstract: This study consists of proposing a new mathematical method to develop a new model for evaluating thermal distributions throughout convergent-divergent channels between non-parallel plane walls in Jeffery Hamel flow. Subsequently, dimensionless equations that govern temperature fields and velocity are numerically tackled via the Runge-Kutta-Fehlberg approach based on the shooting method. Additionally, an analytical study is performed by applying an effective computation technique named Adomian Decomposition Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…The algorithm for RKF-45 order is given as (see [35][36][37] Runge -Kutta technique 4 th order For numerical computations, the flow parameter values are constrained, such as Re = 5, λ = 0.5, Pr = 6.2, Ec = 3, Hs = 0.05, ϕ 1 = 0.05, ϕ 2 = 0.05, ϕ 3 = 0.01 and α = 0.4 (divergent channel), α = −0.4 (convergent channel), S = 0.5 (stretching) and S = −0.5 (shrinking). The obtained numerical results are best match with the existing work of Turkyilmazoglu 27…”
Section: Numerical Procedures With Code Validationsupporting
confidence: 86%
“…The algorithm for RKF-45 order is given as (see [35][36][37] Runge -Kutta technique 4 th order For numerical computations, the flow parameter values are constrained, such as Re = 5, λ = 0.5, Pr = 6.2, Ec = 3, Hs = 0.05, ϕ 1 = 0.05, ϕ 2 = 0.05, ϕ 3 = 0.01 and α = 0.4 (divergent channel), α = −0.4 (convergent channel), S = 0.5 (stretching) and S = −0.5 (shrinking). The obtained numerical results are best match with the existing work of Turkyilmazoglu 27…”
Section: Numerical Procedures With Code Validationsupporting
confidence: 86%
“…The mechanism of heat transport in water/Cu and water/Ag between converging/diverging channel by implementing Least Square Method and thermal radiation, magnetic field effects in the presence of stretching/shrinking effects of the walls reported in Usman et al, 9 Dogonchi and Ganji, 10 respectively. Latest significant investigation regarding heat transport between converging/diverging channel (Akinshilo et al 11 ) under varying physical constraints like porous media effects, internal heat generation/absorption, the dynamics of blood suspended by nanoparticles 12 inside the channel with flexible walls, analytical treatment of heat transfer model through ADM, 13 and different nanofluids prepared by variety of nanoparticles and host solvent with different characteristics are examined by Ullah et al 14 and Kumar et al, 15 respectively. The researchers concluded that the hybrid nanoliquids have unique heat transport mechanism and very useful for future applications.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the thermal energy transport coefficient in forced convection flow inside channels is an area that has long piqued the interest of heat transfer (HT) experts because of the important industrial applications of channel flows. So far, various methods have been proposed by researchers, including the use of grooves, ribs, and turbulators [1][2][3][4][5][6][7][8], as well as magnetic field and electric field [9][10][11][12][13][14][15]. The dimensions, type of working fluid, and arrangement of flow in the exchanger are among the important factors for the performance of heat exchangers.…”
Section: Introductionmentioning
confidence: 99%